Judiciary - Bari, Abdul Aziz; Retire, Mr Retire (Cengage Learning, 2008)
udiciary is a branch of govern ment that is concerned with the administration of justice. It upholds law and order by ensuring that all are equally treated before the law. It is composed of a body of judges in a constitutional system and is always separated from the other two branches of government to guarantee the judicial qualities of objectivity and detachment. In democratic as well as Islamic political systems the independence of the judiciary is regarded as an essential prerequisite of a just and free society